2019–2020 Florida Citrus Production Guide: Blight - Ozgur Batuman; Pamela D. Roberts; Ronald H. Brlansky (EDIS)
Citrus blight is a wilt and decline disease of citrus whose cause has not been determined. This 2-page document is part of the 2019–2020 Florida Citrus Production Guide. Written by Ozgur Batuman, Pamela D. Roberts, and Ronald H. Brlansky, and published Plant Pathology Department, March 2019.